Selective Serotonin Reuptake Inhibitor-Induced Sexual Dysfunction: Current Management Perspectives - Atmaca, Murad (Dove Medical Press Ltd, 2020)
Any type of sexual dysfunction is an important problem in half of the patients with depressive disorder. On the other hand, one to a quarter of people without any depressive disorder experience sexual dysfunction. Antidepressant agents can lead to all types of sexual side effects including arousal, libido, orgasm and ejaculation problems. Selective serotonin reuptake inhibitors (SSRIs) are a widely used class of drugs which are prescribed for the treatment of a variety of disorders, including major depressive disorder, obsessive-compulsive disorder, posttraumatic stress disorder, panic disorder, generalized anxiety disorder, and impulse control disorders. It has been reported that one in eight people have utilized one of the SSRIs in the past 10 years. Some studies reported up to 80% of SSRI-induced sexual side effects. Management of SSRI-induced sexual dysfunction seems to be complex and hard. In this paper, SSRI-induced sexual dysfunction and new perspectives in the management of this problem were reviewed.
Keywords: SSRI; sexual dysfunction; current perspectives